2020
DOI: 10.3390/ijerph17197334
|View full text |Cite
|
Sign up to set email alerts
|

Indoor Thermal Environment Long-Term Data Analytics Using IoT Devices in Korean Apartments: A Case Study

Abstract: IoT-based monitoring devices can transmit real-time and long-term thermal environment data, enabling innovative conversion for the evaluation and management of the indoor thermal environment. However, long-term indoor thermal measurements using IoT-based devices to investigate health effects have rarely been conducted. Using apartments in Seoul as a case study, we conducted long-term monitoring of thermal environmental using IoT-based real-time wireless sensors. We measured the temperature, relative humidity (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 22 publications
0
4
0
Order By: Relevance
“…21 The negative correlation of CO 2 and household air pollution health risk exposure value prevalence may be confounded by temperature and ventilation, as seen in the study of Yun et al (2020) and Argunhan and Aci (2018). 22,23 The study results showed that global carbon dioxide measurements negatively correlated to malaria incidence and NTD in the Philippines. The negative correlation between global carbon dioxide levels and malaria incidence may be confounded by temperature.…”
Section: Correlation Of Global Co 2 Levels With Health Factorsmentioning
confidence: 81%
See 2 more Smart Citations
“…21 The negative correlation of CO 2 and household air pollution health risk exposure value prevalence may be confounded by temperature and ventilation, as seen in the study of Yun et al (2020) and Argunhan and Aci (2018). 22,23 The study results showed that global carbon dioxide measurements negatively correlated to malaria incidence and NTD in the Philippines. The negative correlation between global carbon dioxide levels and malaria incidence may be confounded by temperature.…”
Section: Correlation Of Global Co 2 Levels With Health Factorsmentioning
confidence: 81%
“…The study in Korea investigated the relationship of carbon dioxide in kitchens, living rooms, and bedrooms against temperature among apartments in Seoul. 22 They found that during cooling seasons with an outdoor temperature of above 32°C but less than 36°C, there was a negative correlation of CO 2 and temperature . 21 Meanwhile, the study in Turkey investigated the relationship of CO 2 and particulate matter to temperature and showed a negative correlation of indoor CO 2 (-0.409), PM 10 (-0.324), and PM 5.0 (-0.261) to indoor temperature during spring.…”
Section: Correlation Of Mean Temperature Anomaly With Health Factorsmentioning
confidence: 97%
See 1 more Smart Citation
“…People spend almost 90% of their time indoors. Therefore, the indoor thermal environment is closely related to occupant comfort, well-being, and health [ 1 3 ]. Extreme heat and cold exposure poses health risks, particularly for the elderly, children, and those with chronic illness [ 4 6 ].…”
Section: Introductionmentioning
confidence: 99%